9-O-Acetylation of sialic acids is catalysed by CASD1 via a covalent acetyl-enzyme intermediate - Baumann, Anna-Maria T. (Nat Commun, 2015)
Sialic acids, terminal sugars of glycoproteins and glycolipids, play important roles in development, cellular recognition processes and host–pathogen interactions. A common modification of sialic acids is 9-O-acetylation, which has been implicated in sialoglycan recognition, ganglioside biology, and the survival and drug resistance of acute lymphoblastic leukaemia cells. Despite many functional implications, the molecular basis of 9-O-acetylation has remained elusive thus far. Following cellular approaches, including selective gene knockout by CRISPR/Cas genome editing, we here show that CASD1—a previously identified human candidate gene—is essential for sialic acid 9-O-acetylation. In vitro assays with the purified N-terminal luminal domain of CASD1 demonstrate transfer of acetyl groups from acetyl-coenzyme A to CMP-activated sialic acid and formation of a covalent acetyl-enzyme intermediate. Our study provides direct evidence that CASD1 is a sialate O-acetyltransferase and serves as key enzyme in the biosynthesis of 9-O-acetylated sialoglycans. SUPPLEMENTARY INFORMATION: The online version of this article (doi:10.1038/ncomms8673) contains supplementary material, which is available to authorized users.